Predictors of estimated glomerular filtration rate progression, stabilization or improvement after chronic renal impairment in HIV-positive individuals. (1st June 2017) - Ryom, Lene; Mocroft, Amanda; Kirk, Ole; Reiss, Peter; Ross, Michael; Smith, Colette; Moranne, Olivier; Morlat, Philippe; Fux, Christoph A.; Sabin, Caroline; Phillips, Andrew; Law, Matthew; et al.
Abstract : Objectives: The objectives of this analysis were to investigate predictors of progression, stabilization or improvement in estimated glomerular filtration rate (eGFR) after development of chronic renal impairment (CRI) in HIV-positive individuals. Design: Prospective observational study. Methods: The Data Collection on Adverse events of Anti-HIV Drugs (D:A:D) study participants progressing to CRI defined as confirmed, at least 3 months apart, and eGFR 70 ml/min per 1.73 m 2 or less were included in the analysis. The median of all eGFRs measured 24–36 months post-CRI was compared with the median eGFR defining CRI, and changes were grouped into improvement (>+10 ml/min per 1.73 m 2 ), stabilization (−10 to +10 ml/min per 1.73 m 2 ) and progression (<−10 ml/min per 1.73 m 2 ). Adjusted polynomial regression models assessed odds of better eGFR outcomes after CRI, assuming that eGFR improvement is better than stabilization which in turn is better than progression. Results: Of 2006 individuals developing CRI, 21% subsequently improved eGFR, 67% stabilized and 12% progressed. Individuals remaining on tenofovir (TDF) or atazanavir boosted with ritonavir (ATV/r) 24 months post-CRI had worse eGFR outcomes compared with those unexposed [TDF: 0.47 (0.35–0.63) and ATV/r: 0.63 (0.48–0.82)]. Individuals off TDF for 12–24 months [0.75 (0.50–1.13)] or off ATV/r for more than 12 months [1.17 (0.87–1.57)] had similar eGFR outcomes as those unexposed to these antiretrovirals. Older age, hypertension, later date of CRI and diabetes were associated with worse eGFR outcomes. Conclusion: Current TDF and ATV/r use after a diagnosis of CRI was associated with worse eGFR outcomes. In contrast, TDF and ATV/r discontinuation lead to similar longer term eGFR outcomes as in those unexposed, suggesting that these drug-associated eGFR declines may be halted or reversed after their cessation. Abstract : Supplemental Digital Content is available in the text